Ovulation responses on three oestrus synchronisation protocol and association between progesterone concentration in late pregnancy and litter size of boer goats - Hassan Basri, Abdul Mu'in (2016)
Assessment of goat reproductive systems and application of advanced reproductive technologies (ART), help to improve the goat industry in Malaysia. Oestrus synchronisation (OS) protocols and equipment like real-time ultrasonography (RTU) machine are important component of advance reproductive technologies. The objectives of the current study were to determine the ovulation responses on three oestrus synchronisation protocols and association between progesterone levels with litter size in Boer goats. In Experiment 1, twenty-two (24) fertile and healthy Boer does were divided equally into three groups and each group was treated with one of the three treatments:- T1: CIDR for 14 days and 200 IU of pregnant mare serum gonadotrophin (PMSG) and 0.5 ml prostaglandin (PG) prior to CIDR removal; T2: CIDR for 14 days and 0.5 ml PG prior to CIDR removal; T3: CIDR for 9 days and 200 IU of PMSG and 0.5 ml PG prior to CIDR removal. The oestrus sign was observed from 24 hours after CIDR removal to first sign of oestrus. Both ovaries for all does were examined with a RTU machines for 72 hours at six-hours interval beginning at 24 hours after CIDR removal. Blood samples were collected at four points which were:- 24 hours after CIDR removal, at first time of oestrus sign, at first ovulation and at 72 hours after CIDR removal for progesterone hormonal profile assessment. All does demonstrated (100%) oestrus signs but 25%, 12% and 12% in T1, T2 and T3 respectively did not ovulated. Ovulation responses in terms of mean number of follicles observed before first ovulation, mean size of follicles before first ovulation and mean number of follicle ovulated did not show any significant difference (p > 0.05) among the T1, T2 and T3. The percentage of does with single and multiple ovulations were not significantly different among the three treatments. However, high percentages of multiple ovulations (83%, 86% and 71%, respectively) were recorded for each T1, T2 and T3 as compared to single ovulation. Mean number of follicles ovulated from right and left ovaries were significantly different (p < 0.05) in T3 (2.1 ± 1.0, 0.6 ± 0.5). The mean time of ovulation were recorded between 44.0 ± 2.85 to 47.4 ± 2.78 hours (p > 0.05) among the three treatments calculated from 24 hours after CIDR removal. All treatments showed no significant difference (p > 0.05) for duration of ovulation with 18.0 ± 5.37, 21.0 ± 5.95, 19.2 ± 3.98 hours calculated from 24 hour after CIDR removal for T1, T2 and T3 respectively. Assessment of progesterone hormonal profiles at four points did not show any significant difference (p > 0.05) among the three treatments. In Experiment 2, 5 ml of blood sample from 48 pregnant does were taken approximately two weeks before expected kidding date. The blood samples were analyzed to determine progesterone hormonal profile. After parturation, the number of litter size for each doe were recorded either single, twins or triplets. The mean progesterone concentration showed no significant difference (p > 0.05) that are 17.7 ± 2.9 ng/ml for doe with single kid and 21.4 ± 2.8 ng/ml for does with two or more kids. In conclusion, in Experiment 1, the result of ovulation responses showed no significant differences between Treatment 1 (T1) which was insertion of CIDR for 14 days with the injection of 200 IU of PMSG and 0.5 ml PG prior to CIDR removal ; Treatment 2 (T2), insertion of CIDR for 14 days with the injection of 0.5 ml PG prior to CIDR removal and; Treatment 3 (T3), insertion of CIDR for 9 days with the injection of 200 IU of PMSG and 0.5 ml PG prior to CIDR removal. Meanwhile, in Experiment 2, the high number of litter size did not increase the level of progesterone concentration two weeks before kidding.